Adding maize cobs to vertical subsurface flow constructed wetlands treating marine recirculating aquaculture system effluents: Carbon releasing kinetics and intensified nitrogen removal. (February 2019) - Li, Meng; Sun, Linlin; Song, Xiefa
Highlights: Maize cobs released more COD in seawater than in distilled water. NaOH pretreatment promoted COD releasing, both in seawater and in distilled water. Saline CW with maize cobs lixivium removed NO3 -N efficiently with low effluent COD. Abstract: This study aims to investigate the releasing behaviors of maize cobs with or without alkali (i.e. NaOH) pretreatment in seawater and distilled water, and to evaluate the effects of maize cobs addition (solid biomass and lixivium) on nitrogen removal in saline constructed wetland (CW) treating marine recirculating aquaculture system (RAS) effluents. Results revealed NaOH-treated maize cobs released carbon more efficiently, whether in seawater or in distilled water. Compared to distilled water, seawater conditions promoted carbon releasing. CW with maize cobs biomass and lixivium addition had high NO3 -N removal efficiencies without significant difference, i.e. 94.9 ± 6.0% and 87.1 ± 13.2%, respectively. While CW with maize cobs biomass addition had higher effluent COD concentrations (16.3 ± 3.6 mg L −1 ) compared with those adding lixivium (2.1 ± 0.4 mg L −1 ). The study suggested adding maize cobs lixivium to be feasible and effective way to enhance nitrogen removal in saline CW.